2011
DOI: 10.21101/cejph.a3628
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors of Hepatitis C Infection among Egyptian Blood Donors

Abstract: Background: Surveillance of infectious disease markers in the blood donor population is important in recognizing trends in prevalence and incidence of transfusion related infections in asymptomatic volunteer blood donors.Subjects and Methods: It was a cross sectional study. Samples were collected from volunteer blood donors and questionnaire was designed to collect the risk factors data. The prevalence of hepatitis C antibodies among 1,000 apparently healthy blood donors were determined.Objective: To estimate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
25
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 16 publications
2
25
0
Order By: Relevance
“…Currently, 130 to 170 million people worldwide are infected with HCV, and the annual increase is approximately 3.5 million [1]. It is estimated that about 0.2 to 26% of the general population in different countries are chronically infected by HCV [2][4].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, 130 to 170 million people worldwide are infected with HCV, and the annual increase is approximately 3.5 million [1]. It is estimated that about 0.2 to 26% of the general population in different countries are chronically infected by HCV [2][4].…”
Section: Introductionmentioning
confidence: 99%
“…It was therefore concluded that circumcision has a low risk for HCV transmission,32 because almost everyone in a village had been exposed, but a limited number got infected.…”
Section: Discussionmentioning
confidence: 99%
“…Worldwide, Egypt has the highest number of individuals with hepatitis C infection, with 16.8% of their donors being anti-HCV reactive 44 . However, the prevalence of hepatitis C infection in the general population of developed countries varies from 1-2% 45 .…”
Section: Discussionmentioning
confidence: 99%